Debtor's Legal Consequences of Approval of Motor Over Credit Without the Leasing Party's Knowledge - Hilman Alfiansah; Rahmatiar , Yuniar; Sanjaya , Suyono; Abas, Muhamad (Dinasti Research, 2024)
The Over credit process is a method of purchasing an asset by transferring credit from the initial debtor to the new debtor. In the motorbike overcredit scheme, the first party who transfers their motorbike credit to the second party will receive compensation in the form of cash as a substitute for the down payment or what is usually called Down Payment. Meanwhile, the second party will continue the remaining installments from the previous installments. Transfer of fiduciary guarantees or over credit transfer is the process of transferring ownership of an object along with installment payments that are still on credit to an individual who is a third party. The fiduciary guarantee itself is a security right for an object in the credit process that remains in the control of the debtor. The development of leasing companies is quite rapid in Indonesia, the types of goods financed are increasingly varied, not only in the field of transportation but also expanding to the industrial, telecommunications, agricultural and other sectors. Financing carried out by the leasing party is stated in the credit agreement between the leasing party and the debtor.